China's Response To Indonesia's Policies In The North Natuna Sea - Aldi Wahyudi Bolkiah; Asep Setiawan; Usni Usni (Universitas Serang Raya, 2023)
Problems: The North Natuna Sea has emerged as a point of contention between China and Indonesia. This research delves into the ambiguity and potential conflict within China's response to Indonesia's actions in the region. Purpose: This research aims to examine China's response to Indonesia's North Natuna Sea policies. And also Investigate Indonesia's policy regarding North Natuna Sea map issuance. Methodology: Qualitative research methods are employed, primarily involving an extensive review of existing literature. The analysis relies on a descriptive approach, drawing from foreign policy theory and geopolitical theory. Results/Findings: Indonesia's bold move in 2017, Indonesia officially inaugurated the North Natuna Sea Map. Objectives were clear, demarcate territorial boundaries, maximize resource utilization, and advance maritime ambitions. There is China's Ambiguous Response that took three forms. Coercive Response, China asserted dominance via the controversial Nine Dash Line and military force deployment within Indonesia's Exclusive Economic Zone (EEZ) in the North Natuna Sea. Persuasive Response, Diplomatically, China argued for South China Sea sovereignty, including the Nansha Islands and their waters. President Xi Jinping advocated mutual respect among neighboring countries. Dialogic Response, China engaged in diplomatic dialogues through forums like ASEAN-China Free Trade Area (ACFTA) and ASEAN-China Political Consultative Mechanism (PCM) to reduce regional tensions, seeking mutual agreements.Bottom of Form Paper Type: Geopolitical Issue Keywords: North Natuna Sea, UNLCOS, ZEE